2015
DOI: 10.4236/jep.2015.61005
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation Mapping of Groundwater Contamination in a Rural Village of India

Abstract: Availability of clean water and adequate sanitation facilities are of prime importance for limiting diarrheal diseases. We examined the spatial information on the groundwater quality and sanitation facilities of a village in southern India using Geographic Information System (GIS) tools. Place of residence, position of wells and latrines were mapped and well water samples were tested for microbial contamination (Total Coliform Counts (TCC), Fecal Coliform Counts (FCC) and Fecal Streptococcal Counts (FSC)). A w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
2
15
1
3
Order By: Relevance
“…Studies have shown that in a rural setting, the proximity of latrines to a groundwater body is negatively related to the microbiological quality of the groundwater (Megha et al 2015). Our study also found that the households located closer to an area with open drains were more likely to have poorer water quality, although the estimated effects were very small.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Studies have shown that in a rural setting, the proximity of latrines to a groundwater body is negatively related to the microbiological quality of the groundwater (Megha et al 2015). Our study also found that the households located closer to an area with open drains were more likely to have poorer water quality, although the estimated effects were very small.…”
Section: Discussionsupporting
confidence: 41%
“…Studies have also found a negative relationship between the proximity of latrines to groundwater and the groundwater's microbiological quality in a rural setting (Mahadevan and Krishnaswamy 1984;Megha et al 2015).Groundwater contamination is an even bigger problem in peri-urban areas, where population is dense, drainage systems are not developed, and water infrastructure is located closely to on-site sanitation systems. Pit latrines and sceptic tanks are common types of on-site sanitation facility in rural areas of India and are sources of groundwater contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted around the world heavily criticize the UN's basic notion of safe/improved water sources where potable water quality degradation by a variety of chemical/microbial species is ubiquitous 44,41 . In India, where open defecation practices are rampant, especially in rural areas, the potential for microbial contamination of water resources is a dark reality.…”
Section: Resultsmentioning
confidence: 99%
“…Keberadaan koliform seperti E.coli mengindikasikan adanya patogen penyebab penyakit pada air seperti bakteri, virus dan parasit (Pal, 2014). Megha et al (2015) mendeskripsikan dua mekanisme utama pencemaran air yaitu ketidaksempurnaan distribusi dan rendahnya kesadaran individu memenuhi syarat higienis.…”
Section: Pendahuluanunclassified